The Effect of Self-Regulated Learning, Self-Efficacy and Learning Motivation on Economic Learning Achievement with Gender as Moderating Variable - Noviani, Leny; Istiqomah, Istiqomah; Wibowo, Feri Setyo; Sabandi, Muhammad (Jurnal Pendidikan Progresif, 2023)
The effect of Self Regulated Learning, Self Efficacy and Learning Motivation on Economic Learning Achievement with Gender as Moderating Variable. Objective: This study analyzes whether gender moderates the effect of self-regulated learning, self-efficacy, and learning motivation on economic achievement. Methods: This research is a quantitative research with a correlational. The population in this study was students of Social Studies XI in Boyolali, as many as 1,284 students. This research uses cluster random sampling. The number of samples is 308 students. Data collection techniques using a questionnaire. Data analysis technique uses moderated regression analysis (MRA). Findings: The self-regulated learning variable obtained a t-count: 1.385 <1.656 with a sig. 0.167 > 0.05, self-efficacy variable, t-count: 1.929 > 1.656 with a sig. 0.055 > 0.05. The learning motivation variable obtained a t-count: 2.122 > 1.656 with a sig. 0.035 <0.05. Conclusion: There is no difference in self-regulated learning between male and female students. Gender has a positive but not significant effect on self-efficacy. Gender has a positive and significant influence on learning motivation. Keywords: self regulated learning, self efficacy, motivation, learning achievement, gender.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202303